Tensions at the University and living in liminality: English language teachers navigating through new research expectations - Daron Benjamin Loo; Jonathan tang kum khuan; Jinat rehana begum; Deborah choo (ResearchGate, 2024)
This study examined tensions affecting university English language teachers, and subsequently the liminal space they occupied. In this study, tensions arose because of the introduction and promotion of Scholarship of Teaching and Learning (SoTL) for conducting language pedagogical research. This move had inadvertently displaced existing research perspectives and approaches and compelled a reconfiguration of the teacher’s professional sense of self. There were four English language teachers involved in this study, all of whom were teaching different types of English courses for academic purposes in a public university in Singapore. Data for this study comprised reflections written by the participants, which were analyzed as case studies. Through the examination of tensions and liminality affecting the participants, it became apparent that distinct strategies and coping mechanisms were enacted. There were those who sought to distinguish existing research perspectives, and those who embarked on a productive journey to navigate through the new research requirement. All these constituted professional development for the participants in personalized ways. The examination of the case studies also indicated how top-down research endeavors may be challenged, especially in a field like English language education, given its long-standing and established research traditions. Yet, the circumstance which saw novel research approaches being introduced illustrate how the professional community of English language teachers in the higher education setting remain on the fringes of academia. Future studies should consider taking an ecological approach to examining tension to gain a more comprehensive understanding of English language teachers’ professional identity.